A new species of Bosmina (Liederobosmina) Brték, 1997 (Cladocera: Bosminidae) from high mountain lakes of Colombia - Garibian, Petr G.; Juračka, Petr Jan; Kotov, Alexey A. (Zootaxa, 2021)
Insufficient attention has been recently paid by the taxonomists to the family Bosminidae Baird (Crustacea: Cladocera). Here we describe a new species of Bosmina (Liederobosmina) Brték from high mountain water bodies of Colombia which is unique among all bosminids having heavily striated valves. Most probably, this taxon has a narrow distribution area in the Andean high mountains. It is obvious that the Andean highlands must be studied in detail, i.e. using molecular methods, and more new taxa might be detected in the future.